Novel albumin-binding multifunctional probe for synergistic enhancement of FL/MR dual-modal imaging and photothermal therapy - Yu, Cheng; Ding, Zhuyuan; Liu, Huan; Ren, Yulu; Zhang, Minping; Liao, Qiuling; Luo, Tao; Gao, Lujing; Lyu, Shiyi; Tan, Huiwen; Hu, Linan; Chen, Zhu; et al. (Frontiers in Chemistry, 2023)
The fluorescence/magnetic resonance (FL/MR) dual-modal imaging could provide accurate tumor visualization to guide photothermal therapy (PTT) of cancer, which has attracted widespread attention from scientists. However, facile and effective strategies to synergistically enhance fluorescence intensity, MR contrast and photothermal efficacy have rarely been reported. This study presents a novel multifunctional probe Gd-EB-ICG (GI) for FL/MR dual-modal imaging-guided PTT of cancer. GIs can self-assemble with endogenous albumin to form drug-albumin complexes (GIAs), which exhibit excellent biocompatibility. Albumin can protect GIAs from the recognition and clearance by the mononuclear phagocytic system (MPS). High plasma concentration and long halflife allow GIAs to accumulate continuously in the tumor area through EPR effect and specific uptake of tumor. Because of the prolonged rotational correlation time (τR) of Gd chelates, GIAs exhibited superior MR contrast performance over GIs with more than 3 times enhancement of longitudinal relaxation efficiency (r1). The fluorescence quantum yield and photothermal conversion efficiency of This is a provisional file, not the final typeset article GIAs was also significantly improved due to the constrained geometry, disrupted aggregation and enhanced photothermal stability. This simple and feasible strategy successfully resulted in a synergistic effect for FL/MR dual-modal imaging and photothermal therapy, which can cast a new light for the clinical translation of multifunctional probes.